Youth Migration in the Tamang Community of Kakani Rural Municipality (Pragyaratna प्रज्ञारत्न, 2025)
Migration is the movement of people from one place to another in search of a better life. Youth migration refers explicitly to the process of moving, especially among young people aged 15 to 24 years. This study examines the reasons behind youth migration within the Tamang community in Kakani Rural Municipality, Nuwakot District. To achieve this, data were gathered using a case study approach within a qualitative framework. In-depth interviews and observations were conducted with seven family members from the Tamang community to gain an understanding of their experiences with youth migration. The study is guided by conflict theory and presents youth migration not only as an individual choice but also as a consequence of structural inequalities, resource struggles, and societal power dynamics. The migration of Tamang youth was primarily driven by factors such as lack of employment opportunities in the village, economic hardship, poor quality education, peer and family pressure, disinterest in traditional work, and the search for a more secure future. Therefore, implementing local employment programs aimed at youth in rural areas may help to reduce this migration trend to some extent.